Queen lipid content and nest growth in the leaf cutting ant (Atta sexdens rubropilosa) (Hymenoptera: Formicidae) - da Silva Camargo, Roberto [UNESP]; Forti, Luiz Carlos [UNESP] (Taylor & Francis, 2013)
The relationship between the queens' lipid content and nest growth (population size, biomass and nest architecture) was studied from founding up to 1 year. Nests aged 3, 4, 5, 6, 9 and 12 months were dug in the field, and their dimensions were measured. The ant nest population and fungus garden was also collected. The sample was taken to the laboratory where we counted the worker population and weighed the biomass (fungus plus offspring) and queens. Queens were separated for the determination of lipids. The lipid content in the bodies of queens decreased in the first months, then stabilized (at 4-6 months) before increasing in months 9 and 12. Nest biomass (symbiotic fungus and offspring) and worker population increased over time. The structural growth of the nests was observed by excavating around them. Initially nests (3 months old) had one chamber at an average depth of 15 cm. By 1 year, the nests had three or four deep chambers, and were about 3-4 m deep. Our study contributes to knowledge of the dynamics of the energy-reserve expenditure by queens during colony founding and colony development for up to 1 year. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Atta sexdens; leaf-cutting ants; nest; ant; biomass; colony structure; developmental biology; lipid; population size; queen; stabilization; worker caste; Atta; Atta sexdens rubropilosa; Formicidae; Fungi; Hymenoptera